FEATURES OF AGRICULTURAL ACTIVITY IN MODERN CONDITIONS OF BUSINESS - Levandivskyi , O.T. (The actual problems of regional economy development, 2017)
The article analyzes the approaches of economists to the study of agricultural activity in modern economic conditions. The genesis of this problem shows the main approaches. It is noted that modern agriculture is closely connected with investment activity. The zonal systems of agricultural production management based on functional and organizational subsystems of agricultural production are grounded. In this case, the functional subsystems reflect directly the content, as separate stages, and in the whole process of production itself. In scientific researches most often distinguish technological, ecological, economic and social functional subsystems, the form of functioning of which is reflected in organizational subsystems. It is noted that when organizing and conducting agricultural production, as well as developing measures to improve its organizational and economic mechanism, it is necessary to take into account the peculiarities of agricultural activity without which it is impossible to achieve a high level of production efficiency.